El bosque tropical caducifolio de la vertiente sur de la Sierra de Nanchititla, estado de México: la composición y la afinidad geográfica de su flora - Zepeda Gomez, Carmen; Velazquez Montes, Ernesto (Instituto de Ecología, A.C., 1999)
A check list of vascular plants consisting of 89 families, 208 genera and 288 species is presented. The study area, called Sierra de Nanchititla, is located in the southwestern region of the State of Mexico, near the borders with Guerrero and Michoacán. The families Asteraceae, Pteridaceae, Burseraceae, Fabaceae, Mimosaceae and Rubiaceae are best represented. Geographical distribution of families and genera is analyzed. The elements of tropical affinity are dominant. Complementary data on phenology of some life forms are provided as well as information about the state of conservation of original vegetation.